A note on the mean-field limit for the particle swarm optimization. (July 2021) - Huang, Hui
Abstract: Recently a continuous description of Particle Swarm Optimization (PSO) based on a system of stochastic differential equations was proposed in Grassi and Pareschi (2020) for solving global optimization problems. This note is devoted to solving the open problem suggested in Grassi and Pareschi (2020) by providing a rigorous proof of the large particle limit under the assumption of finite second moment.